Development of Motorcycle Electricity System Trainer Media in Class XI TBSM SMK N 5 Pekanbaru - Sonsang Sonsang; Arden Simeru (Postgraduate School, Universitas Negeri Padang, 2022)
One of the existing subjects in the TBSM study program is the maintenance of electricity motorcycles taught in class XI and XII, some basic competencies in this Subject are maintaining system charging, maintaining system ignition, system injection, system starter, and still many again. Based on observation beginning obtained not enough understanding it students in Mastering Subjects Maintenance Electricity Proven Motorcycle results in study students are almost 50 percent student did not pass one reason low percentage completeness score students in the eyes lesson Maintenance Electricity Motorcycle is its hard student in understanding Theory it is because no interestingly the learning media used, plus again Theory system electrician this relate with Suite lots of cables because it was developed a media Trainer system electricity this for can Becomes solution from the problem this. Based on the background behind here base learning media development system electricity motorcycle-based Trainer, is expected to result in study students could increase from before. Method research used is method Research & Development (R&D) type 4D. In research this, the researcher develops something product in the learning process System Electricity Motorcycles in Class XI TBSM SMK N 5 Pekanbaru. System Trainer practicality test results electricity motorbikes for teachers and students with a statement on indicator convenience use response tool positive by teachers and students, with so the system Trainer electricity motorbikes can use as a medium in learning. Teachers still can develop and use tools this not only limited recognize names, functions, and method work components, but also can do disturbance as well as the solution.